PENGARUH BUDAYA KERJA DAN KEPUASAN KERJA TERHADAP KINERJA ASN DENGAN LINGKUNGAN KERJA SEBAGAI VARIABEL MODERASI PADA DINAS LINGKUNGAN HIDUP KABUPATEN SITUBONDO - Yonata, Chandra Fajri; Ediyanto, Ediyanto; Tulhusnah, Lusiana (Fakultas Ekonomi dan Bisnis, 2024)
The Situbondo Regency Environmental Service (DLH) has a strategic role in carrying out regional government tasks in the environmental sector based on the principle of regional autonomy. This research aims to analyze the influence of Work Culture, Job Satisfaction and Work Environment on ASN Performance at the Situbondo Regency Environmental Service. The population in this study were ASN at the Situbondo Regency Environmental Service. This research was carried out using a quantitative approach and a sampling technique determined by probability sampling using the Slovin method, which means that the population size in this study reached a size that met the error requirement of 10%. The results of hypothesis testing using the Smart PLS 3.0 application show that Work Culture has a positive and significant effect on Performance, Job Satisfaction has a positive but not significant effect on Performance. Hypothesis test results moderated by the Work Environment variable have a negative effect in moderating Work Culture on Performance but are not significant, the Work Environment variable has a positive effect in moderating Job Satisfaction on Performance but is not significant.